Oxfam journal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Earlier this year Oxfam brought out a new journal, Development in practice, which aims to stimulate debate about overseas development from the perspective of non-governmental organizations. It will offer objective assessments of Oxfam's own...